The Usefulness of Zhukovsky Double Balloon in Obstetric Hemorrhage - Sergey V. Barinov; Irina V. Medyannikova; Anna V. Borisova; Yulia I. Tyrskaya; Irina V. Savelieva; Inna V. Shamina; Oksana V. Lazareva; Tatyana V. Kadtsyna; Nan Zhang; Yang Pan (Wolters Kluwer Health, 2019)
Abstract. Objective:. To evaluate the effectiveness of the use of a modified Zhukovsky double (vaginal and uterine) balloon to improve the results of treatment in women with obstetric hemorrhage. Methods:. We conducted an observational controlled study including 701 puerperas, which were divided into two groups: The main group consisted of 508 women, who underwent a combined management, that is, traditional (transfusion of fresh frozen plasma, erythrocyte mass, uterotonics, hemostatic agents), surgical hemostasis in cases of caesarean section, and insertion of a double Zhukovsky balloon; while the comparison group included 193 patients, who were managed traditionally. The main group and the comparison group were divided into subgroups according to the main etiology of obstetric hemorrhage: IA and IB-postpartum; IIA and IIB-placenta accreta; IIIA and IIIB-postpartum hysterectomy. Results:. The most frequent causes of massive obstetric hemorrhage were atony of the uterus (39.2%), placenta previa (29.1%), and placental abruption (11.5%). Of the 508 balloon insertions, 345 (70.7%) were inserted for hemorrhage during cesarean section and 148 (29.3%) for obstetric hemorrhage after spontaneous delivery. Among the obstetric hemorrhage at caesarean section, lower segment bleeding prevailed (78.1%), caused mainly by placenta previa, placenta accreta, placental abruption, polyhydramnios, and uterine scar defects. Combined management, including surgical hemostasis and insertion of vaginal and uterine balloon of Zhukovsky, reduced blood loss by 1.5 times and the number of hysterectomies by 6.72 times compared to controls. Conclusion:. The use of a modified Zhukovsky double balloon in the management of obstetric hemorrhage may reduce the number of hysterectomies and the amount of blood loss.